2017
DOI: 10.1371/journal.pone.0173482
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analysis and functional annotation of positional candidate genes for feed conversion efficiency and growth rate in pigs

Abstract: Feed conversion efficiency is a measure of how well an animal converts feed into live weight and it is typically expressed as feed conversion ratio (FCR). FCR and related traits like growth rate (e.g. days to 110 kg—D110) are of high interest for animal breeders, farmers and society due to implications on animal performance, feeding costs and environmental sustainability. The objective of this study was to identify genomic regions associated with FCR and D110 in pigs. A total of 952 terminal line boars, showin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…This biological mechanism is also related to insulin response (Richardson & Herd, 2004), which supports the relationship between insulin genes and FE, as previously stated. Indeed, several lipid‐related genes were identified, such as SDCBP (Santos, 2018), ACLY (Ji, Osorio, Drackley, & Loor, 2012), OLR1 (Vinsky, Islam, Chen, & Li, 2013), CRTC3 (Raza et al., 2019), PRKDC (Horodyska, Hamill, Varley, Reyer, & Wimmers, 2017), HNRNPA3 (Wang et al., 2018), HTATIP2 (Liao et al., 2014) and NFE2L2 (Wu, Cui, & Klaasen, 2011) genes. The OLR1 and CRTC3 genes were reported associated with body weight, rib eye area and fat thickness in Nellore (Fonseca et al., 2015), and fat deposition in Qinchuan cattle (Raza et al., 2019), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This biological mechanism is also related to insulin response (Richardson & Herd, 2004), which supports the relationship between insulin genes and FE, as previously stated. Indeed, several lipid‐related genes were identified, such as SDCBP (Santos, 2018), ACLY (Ji, Osorio, Drackley, & Loor, 2012), OLR1 (Vinsky, Islam, Chen, & Li, 2013), CRTC3 (Raza et al., 2019), PRKDC (Horodyska, Hamill, Varley, Reyer, & Wimmers, 2017), HNRNPA3 (Wang et al., 2018), HTATIP2 (Liao et al., 2014) and NFE2L2 (Wu, Cui, & Klaasen, 2011) genes. The OLR1 and CRTC3 genes were reported associated with body weight, rib eye area and fat thickness in Nellore (Fonseca et al., 2015), and fat deposition in Qinchuan cattle (Raza et al., 2019), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The phenotypic measurements of FCR, ADFI, and RFI are difficult and costly which need an automatic feeding system. Besides, the selection of single FE related traits may affect other traits that are valuable for pig production, such as growth rate ( Horodyska et al, 2017 ). This conundrum makes the genetic investigation of FE very important.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed many potential candidate genes for FE related traits in pigs. For FCR, several researchers reported that significant SNPs and QTLs were mainly located on chromosomes (SSC) 4, 6, 7, 8, 17, and 18 ( Sahana et al, 2013 ; Horodyska et al, 2017 ). Another study identified three QTLs for ADG, which were located on SSC 4, 14, and 15 ( Ji et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“… 52 when compared to lesser muscled counterparts 52 . DIS3 , a gene nearby to a variant associated with RFI in the current study, encodes a protein involved in RNA metabolism 53 and has been linked with feed conversion efficiency in pigs 54 .…”
Section: Discussionmentioning
confidence: 74%